The nature of history - Marwick, Arthur (Houndmills, Basingstoke, Hampshire : Macmillan Education, 1989)
Developed for students and general readers looking for a concise guide to the methods and purposes of historical study, this book seeks to explore the nature of historical evidence, to show how history comes to be written and to offer a basis on which "good" history can be distinguished from "bad."
Includes bibliographical references.
Keywords: Historiography; Peace-building -- History